PERANAN KATEKESE DALAM MENINGKATKAN PEMAHAMAN UMAT PAROKI SANTO YOHANES PEMANDI NAESLEU TENTANG SIKAP TUBUH DAN TATA GERAK LITURGI DALAM TERANG DESIDERIO DESIDERAVI - Sabu Ola, Maria Inosensia; Metom, Philipus Benitius; Aek Klau, Yohana Aek Klau (Sekolah Tinggi Pastoral St. Petrus Keuskupan Atambua, 2024)
Movements in the liturgy are an important part of a celebration of faith. The same or uniform body posture depicts the unity of the people who are gathered to celebrate the liturgical celebration. However, in reality there are still many people who do not follow the correct and appropriate body postures and movements when participating in liturgical celebrations. This problem then became the concern of the universal Church. Pope Francis published the apostolic letter Desiderio Desideravi with the intention of providing instructions or signals for contemplation of the beauty and truth of the Eucharistic celebration. Based on these problems, the formulation of the problem in writing this thesis is: What is the role of catechesis in increasing the understanding of the parishioners of Saint John Pemandi Naesleu regarding body posture and liturgical movements in the light of Desiderio Desideravi? The purpose of writing this thesis is to determine the understanding of the parishioners of Saint John Pemandi Naesleu regarding bodily postures and liturgical movements, to understand the role of catechesis in increasing the congregation's understanding of the attitudes and movements of the liturgy, and to understand the appreciation of the ParishionersSt. John the Bath of Naesleu on bodily postures and liturgical movements in the light of Desiderio Desideravi. The model used in this research is a descriptive model with qualitative research methods. Qualitative research is a research method used to examine objects of social phenomena that occur naturally, where researchers will analyze data obtained from the field based on data collection techniques, namely interviews, observation and documentation. Based on the results of observations and interviews, researchers found that the understanding of St. Yohanes Pemandi Naesleu regarding body posture and liturgical movements before carrying out catechesis is still very lacking. Even though in participating in the liturgical celebration, all the people are actively involved. However, after the implementation of catechesis, the people were interviewed again, the people's answers showed that the people's understanding had increased and was much better than the previous answers. From the entire description above, it can be concluded that the congregation's understanding of body postures and liturgical movements can increase if catechesis activities are carried out continuously specifically regarding body postures and liturgical movements.